Ultrasonic Irradiation during the Calcium Sulfate Hemihydrate to Dihydrate Transformation Process - SAYAN, PERVİZ; POLAT, SEVGİ (WILEY-V C H VERLAG GMBH, 2019)
The ultrasound-assisted transformation of calcium sulfate hemihydrate (CSH) to calcium sulfate dihydrate (CSD) was studied using three ultrasonic power settings. In addition to continuously measuring the variation in the conductivity value with time, the process was followed by X-ray diffraction and scanning electron microscopy (SEM) analysis. Thermogravimetric analysis, Fourier transform infrared, mass spectrometry, and filtration analyses helped to determine the physicochemical properties of the as-obtained crystals. The morphological changes in the surface morphology were observed by SEM. The experimental results indicate that ultrasonic irradiation and its intensity have a significant effect on the crystal size, morphology, adsorption, and filtration characteristics. Mandelic acid in combination with ultrasonic irradiation can be used as an accelerator for the transformation process from CSH to CSD.
Keywords: Calcium sulfate dihydrate; Crystallization; Ultrasonic irradiation; Ultrasound-assisted transformation; CRYSTALLIZATION; BASSANITE; HYDRATION; GYPSUM; AL3+